﻿A new freshwater amphipod (Arthropoda, Malacostraca, Amphipoda, Gammaridae), Echinogammarus ozbeki sp. nov. from the Tomara Waterfall, Turkey - Hazel Baytaşoğlu (ZooKeys, 2023)
A new species of freshwater amphipod, Echinogammarus ozbeki sp. nov., collected from Tomara Waterfall, Gümüşhane province, northeastern Anatolia, is described and illustrated. The new species belongs to the genus Echinogammarus and exhibits characteristic uropod 3 features of that genus. Some of the distinctive features of the Echinogammarus ozbeki sp. nov. species are a small body length, urosome segments without dorsal elevations, distal end of the peduncle segments of antenna 1 with setae longer than the diameter of the segment, presence of strong spines accompanying setae on both inner and outer margin of exopod, and uropod 3 parviramous.